PENERAPAN METODE SQ3R MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA SDN 002 TOAPAYA - Zasnimar, Zasnimar (Jurnal Pembelajaran Prospektif, 2020)
In learning to read, it involves students to be active with teacher’s guidance, so that the concepts on the subject can be understood, so as to improve students' reading skills. By improving reading skills through the use of SQ3R learning method, students are expected to be able to solve problems, make decisions, think critically, and think creatively so that students’ learning outcomes can also be improved. The SQ3R method is expected that students can understand andremember the material in a longer / permanent period of time. The use of the SQ3R method in learning will feel more interesting so that it can increase motivation to understand a reading. In essence, reading is a physical and mental activity to find the meaning of writing, although in that activity there is a process of recognizing letters. Based on the two opinions above, the researcheragrees that reading involves many things including physical, namely the eyes, involving mental, namely thoughts, especially perception and memory. To achieve the goal of reading, it requires not only the ability to understand what is implied but also the skills to understand what is implied in a reading text.